PENGARUH PENGUASAAN KOMPETENSI GURU, MOTIVASI KERJA, DAN PENGUASAAN TEKNOLOGI INFORMASI TERHADAP KINERJA KERJA GURU SEKOLAH DASAR NEGERI DI KECAMATAN SALAMAN KABUPATEN MAGELANG DI KECAMATAN SALAMAN KABUPATEN MAGELANG (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
Influence Mastery Teacher Competence, Work Motivation and Information Technology Performance Against Public Elementary School Teachers in District Magelang Regency Salaman 2014.Tesis Year Management Studies Bachelor of Education Program Pascasarjana Wiyata Park University students Yogyakarta Teacher performance is closely related to the quality of education, so it is important to evaluate the activities that have been carried out by the teachers in order to produce quality Pendidika Goals to be achieved preformance of this study is to know the how much Influence Mastery Teacher Competence, Work Motivation da Mastery of Information Technology on Performance State Primary School teachers in the district of Magelang District 2014 Salaman both together (simultaneously) or in parsial.Selanjutnya this study also analyzed the moderating role of Magelang District Education Office on the effect of these three variables on the Performance of State Primary School Teachers in District Salaman Magelang District 2014. The population in this study were all teachers in the district School State Primary in District Magelang Regency Salaman District 2014, amounting to 375 person sample is determined based on the table of determining the number of samples that developed from Isaac and Michael that as many as 170 people, the number of samples from each school is determined by the method Purporive Random Sampling and Determination of respondents using simple random sampling method .Penelitian this process the primary data collected through the data kuesioner.Untuk determine the effect of independent variables on an depend- ent variable is done by F test at a significance level of 5% . Statistical analysis showed that the variables are the same Teacher Competence Mastery, Mastery Technology Work Motivation and Information on Performance in District Magelang Regency Salaman 2014 with regression value of 52.27%, this figure shows bahwa52,27% of teacher performance is determined three variables the while the remaining 47.73% is determined by other variables outside the control of the variable partial model.Secara teacher competency contribute effectively (SE) of 14.29%, 21.015% of work motivation and mastery of information technology by 14.77% in determining the performance of State Primary School teacher in District Magelang Regency Salaman 2014.